Магнитные аномалии и модель распределения намагниченности в земной коре приполярного и полярного секторов Уральского региона - Федорова, Н.В.; Рублев, А.Л.; Муравьев, Л.А.; Колмогорова, В.В. (Геофизический журнал, 2017)
Розглянуто результати вивчення структурних особливостей аномального магнітного поля в межах приполярного і полярного секторів Уральського регіону Виділено аномалії від різних шарів земної кори і побудовано карти аномальних полів. У межах осадових басейнів карту локальних аномалій використано для картування базит-ультрабазитових масивів у верхніх частинах фундаменту. Проведено інтерпретацію регіональних магнітних аномалій. The study of the structural features of the anomalous magnetic field for the territory of the circumpolar and polar sector of the Urals region was carried out. The anomalies of the Earth's crust layers were identified and the maps of such anomalies were created. Map of local anomalies was used for mapping basic-ultrabasic massifs in the upper parts of the foundation within the sedimentary basins. An interpretation of regional magnetic anomalies was carried out, a model structure of the Earth's crust and their parameters are based on the results of the studies along the DSS profiles.